(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Budiman LF, Apriyanto A, Pancoro A, Sudarsono S. 2019. Genetic diversity analysis of Tenera × Tenera and Tenera × Pisifera Crosses and D self of oil palm (Elaeis guineensis) parental populations originating from Cameroon. Biodiversitas 20: 937-949. There are three types of oil palm (Elaeis guineensis Jacq.) based on the shell thickness, such as the Dura (D type, with a thick shell), the Pisifera (P type, with no or very thin shell) and the Tenera (T type, with medium shell thickness), respectively. The T type is a commercially grown oil palm, originated from hybridization between D × P types. The success of oil palm breeding depends on the availability of diverse parental populations, especially in the D and the P types. Unfortunately, the improved P type of oil palm may only be produced by crossing between Tenera (T × T) or between Tenera and Pisifera (T × P) while improved D type may easily be produced from selfing of a single Dura type palm (D self). Therefore, evaluation of the potential genetic diversity of Dura parental lines derived from D self and Pisifera lines derived from T × T or T × P is essential. The objectives of this research were to analyze the genetic diversity of T × T, T × P and D self oil palm progenies originated from Cameroon which would be used as parental population for breeding the commercial T types of oil palm in Indonesia, determine whether the progenies were from legitimate hybrids of the desired parents and evaluate their potential values for creating Tenera hybrid in the oil palm breeding programs. A total of 148 individuals from one combination of T × T and two T × P crosses and three D self-pollinations were evaluated. Genotyping was conducted using 16 SSR marker loci. The genotype data were analyzed using software for population genetic and genetic diversity analysis. Results of the analysis indicated the evaluated 16 SSR marker loci were either highly or moderately polymorphic based on their Polymorphic Information Content (PIC) values. Hence, they could be used for genetic diversity analysis of the evaluated oil palm progenies. Both the T × T and T × P progenies were more diverse than the D self-ones. Clustering and Principle Component Analysis (PCA) showed that all populations were grouped into three groups consisting of (1) B02 – T × P progenies, (2) B57 – T × T progenies, and (3) the rest of the populations (a mixture of the B01 – T × P progenies, and the three D self progenies). Moreover, the third group was further divided into five sub-groups, consisting of sub-group 3.1: the B01 progenies, and sub-group 3.2 to 3.5 comprising of a mix of individuals from members of at least two different D self progenies. All the studied T × T and T × P progenies could potentially be used as improved male parents for producing future Tenera oil palm hybrid varieties. The T x T and T × P progenies had a wider genetic distance than that of the D self progenies. Moreover, for practical breeding purposes, the members of D self oil palm progenies should not be grouped based only on the family but should be based on the results of the clustering analysis. The reported data should be beneficial for aiding future oil palm breeding in Indonesia.